PENGARUH SOSIAL MEDIA TERHADAP PERKEMBANGAN EMOSIONAL SISWA MTs AT-TAQWA KALANGANYAR - Hakim, M. Alimul; Miftahul Munif, Moh. Vito (-, 2025)
Social media is a group of internet-based applications that allow people to interact. Social emotional development is the learning process of students who adapt to understand situations and feelings when interacting with people in their environment. This is obtained by listening, observing and imitating what they see. Almost all MTs AT TAQWA Kalanganyar students play social media, they say they often play on cellphones. The aim of this research is to determine the influence of social media on the emotional development of MTs AT TAQWA Kalanganyar students. This research uses quantitative correlation research with questionnaire data collection. The data analysis methods used are validation tests, reliability tests, normality tests, and T tests (hypothesis tests). Data processing in this study used the SPSS 25 application. The results of this study showed that there was no significant influence between the Influence of Social Media on Students' Emotional Development. This is in accordance with the researchers' calculations using the SPSS 25 application, which used the correlation test to obtain a t-count value < t-table, namely 1,179 < 2,022. So there is no significant correlation between the influence of social media on the emotional development of students at MTs AT TAQWA Kalanganyar.